PENGARUH MODAL USAHA, LITERASI KEUANGAN, DAN KUALITAS LAPORAN KEUANGAN TERHADAP KEBERLANJUTAN UMKM DI DESA WISATA KREBET SENDANGSARI PAJANGAN BANTUL - Edi Saputra; Hasim As’ari (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the influence of business capital, financial literacy, and the quality of financial reports on the sustainability of MSMEs in the Krebet Sendangsari Pajangan Tourism Village, Bantul. The phenomenon underlying this research is the still low level of financial understanding and limited business capital that hinder the sustainability of MSMEs. The research method used is a quantitative approach with multiple linear regression analysis techniques. Primary data were obtained by distributing questionnaires to 57 respondents of bamboo craftsmen MSMEs. The results of the analysis indicate that the three independent variables, namely business capital, financial literacy, and the quality of financial reports, have a positive and significant effect on the sustainability of MSMEs. These findings indicate that increasing capital capacity, financial understanding, and the preparation of quality financial reports can strengthen the resilience and sustainable growth of MSMEs. This research is expected to serve as a reference for business actors, financial institutions, and the government in designing strategies to increase the capacity of MSMEs in the rural creative economy sector